A Review of Isolation Attack Mitigation Mechanisms in RPLBased 6LoWPAN of Internet of Things - Rajasekar, V.R.; Rajkumar, S. (Computer Assisted Methods in Engineering and Science, 2024)
The Routing Protocol for Low-Power and Lossy Networks (RPL) is an open standard routing protocol defined by the Internet Engineering Task Force (IETF) to address the constraints of IPv6 over Low-Power Wireless Personal Area Networks (6LoWPAN). RPL is susceptible to various attacks, including isolation attacks, in which a node or a set of RPL nodes can be isolated from the rest of the network. Three significant isolation attacks are the black hole attack (BHA), selective forwarding attack (SFA), and destination advertisement object (DAO) inconsistency attack (DAO-IA). In a BHA, a malicious node drops all packets intended for transmission silently. In an SFA, a malicious node forwards only selected packets and drops the other received packets. In a DAO-IA, a malicious node drops the received data packet and replies with a forwarding error packet, causing the parent node to discard valid downward routes from the routing table. We review the literature on proposed mechanisms, propose a taxonomy, and analyze the features, limitations, and performance metrics of existing mechanisms. Researchers primarily focus on power consumption as the key performance metric when mitigating BHA (47%), SFA (51%), and DAO-IA (100%), with downward latency being the least addressed metric for BHA (4%) and SFA (3%), and control packet overhead being the least addressed for DAO-IA (37%). Finally, we discuss the unresolved issues and research challenges in mitigating RPL isolation attacks.